“You’re such a good friend”: A woven autoethnographic narrative discussion of disability and friendship in Higher Education - Castrodale, Mark Anthony; Zingaro, Daniel (Disability Studies Quarterly, 2015)
In this article, the authors discuss friendship as a method of qualitative inquiry. After defining friendship and positing it as a kind of fieldwork, the methodological foundations of friendship as method are established (Tillmann-Healy, 2003). The purpose of this narrative woven autoethnographic study is to examine the role of friendship in describing disabling physical and attitudinal access barriers in a university setting. Friendship represents a critical analytic lens through which disabled/nondisabled individuals alike may examine their positions, understandings, regimes of practices, and particular knowledges. Friends —Mark and Dan — discuss their experiences of disablement and reflections on dis/ability. The authors draw from their experiences of friendship and disability in higher education and their allied identities to discuss and examine questions of access, disclosure, and inclusion.